2019
DOI: 10.33271/mining13.04.114
|View full text |Cite
|
Sign up to set email alerts
|

Study of change in the leaching solution activity after treatment with a cavitator

Abstract: Increasing the valuable component content in a pregnant solution due to the activation of leaching solution with cavitation treatment in case of the borehole in-situ leaching (ISL). Methods.To obtain the cavitation effect, a laboratory cavitation plant has been produced. Studies on the sulphuric acid solution activation by means of cavitation were conducted using solutions with 10 g/l of acid content. Studies of changing the sulphuric acid solution activity during treatment with a cavitator were conducted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…In [7], we found that the use of the cavitation effect leads to an increase in the content of the useful component in the productive solution. However, in the course of the conducted studies, it was found that with an increase in the degree of cavitation, the density of the leaching solution changes, which can lead to a change in the gravity and, accordingly, the process of precipitation of the productive solution.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In [7], we found that the use of the cavitation effect leads to an increase in the content of the useful component in the productive solution. However, in the course of the conducted studies, it was found that with an increase in the degree of cavitation, the density of the leaching solution changes, which can lead to a change in the gravity and, accordingly, the process of precipitation of the productive solution.…”
Section: Introductionmentioning
confidence: 96%
“…To the mining group of JSC NAK Kazatomprom includes 16 enterprises with full andpartial ownership thatare developing 20 underground minesin-situ leaching. Uranium deposits are located on the territories of South Kazakhstan, Kyzylorda and Akmola regions [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of different techniques intensifying leaching has shown that they accelerate the process and increase several times useful mineral extraction [28], [29]. Nevertheless, they are not versatile and depend upon conditions of specific deposits.…”
Section: Introductionmentioning
confidence: 99%
“…It is unacceptable that a state that has its own coal resources exports it from Russia and Kazakhstan. In Kazakhstan coal still remains and will definitely remain the main source of energy in the near future, despite the fact that the country is a world leader in uranium mining [2], which has been increased several times over the past 15 years due to underground leaching [2,3]. As a result, a considerable share of the country's export is accounted for uranium, coal and electricity.…”
Section: Introductionmentioning
confidence: 99%